The existence of policy regulations and the court's authority to review policy regulations (beleidsregel) - Muhammad Ali Hasan; Anna Erliyana (Trigin Publisher, 2023)
Policy regulation (beleidsregel) is a legal product that is based on the expertise/discretion of the government in making policies because of the law. Policy regulations are outlined in various forms, including in the form of circulars, guidelines, announcements, decrees that are general and abstract in nature and even in the form of regulations which are referred to as pseudo regulations (pseudo legislation). Legal developments then gave birth to policy regulations that were formed based on the mandate of statutory regulations. In a rule-of-law state, every policy that binds society must be subject to review in court, including policy regulations, which then creates differences of opinion about who has the authority to implement policy regulations, bearing in mind that until now there are no laws and regulations that regulate rigidly regarding the formation policy regulations and their testing mechanisms.